Evaluating Learning Community Programs for Teacher Professionalism Using the Cipp Model - Ibnu Muthi; Imam Suseno (Sakura Digital Nusantara, 2026)
n the era of disruption and the 4.0 industrial revolution, educators should think about the balance of hard skills and soft skills to avoid boring and demagogic learning processes, which might decrease human dignity. This research is aimed at in-depth evaluation of the efficiency of the